Potential antiangiogenic property, brine shrimp toxicity and phytochemical screening of different varities of cassava (Manihot esculenta Crantz) leaf extracts - Velado, Irene B. (2016.)
Cancer has been one of the diseases that increases mortality rate every year. It is highly dependent on tumor growth and angiogenesis. The study of plant extracts as angiogenesis has been a stepping stone to in the treatment of tumor progression. Cassava (Manihot esculents Crantz) is a staple food and is mainly used for human consumption. It is traditionally used as antihelminthic, anti-inflammatory and antimicrobial. Thus, this study was designed to investigate the antiangiogenic and cytotoxicity of the different varieties of cassava leaves using chorioallantoic membrane (CAM) assay and brine shrimp cytotoxicity test. Eggs were treated with volumes of 20 µL, 30 µL and 50 µL. The average blood vessel count generated was compared to untreated samples and phosphate buffer saline solution. Probit analysis was done to obtain the LC50 value of the extracts. The calculated LC50 values of different cassava leaf extracts were 498.99 µg/mL for CLMY, 602.80 µg/mL for CLYY, 414.89 µg/mL for CLMW and 339.72 µg/mL for CLYW which is lower than 1000 µg/mL which signifies that the extracts were potent. In CAM assay, cassava leaf extracts showed lower average blood vessel count than the untreated sample and phosphate buffer saline solution. Statistical analyses showed the significant difference between the ethanolic extracts, untreated samples and phosphate buffer saline solution. The mature cassava leaves with red petiole showed the lowest average blood vessel count. Furthermore, the phytochemical screening of extracts revealed the presence of alkaloids, glycosides, steroids and triterpenoids, flavonoids, terpenoids, saponins, phenols, and tannins.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cassava (Manihot asculenta Crantz); Cassava -- leaf extracts; Phytochemical -- Screening; Antiangiogenesis; Brine shrimp; Cytotoxicity